Detection Rate of Endometrial Cancer by Endometrial Thickness, and Relationship between the Thickness and Myometrial Invation of Endometrial Cancer in Patients with Postmenopausal Bleeding - KARASAWA Tetsuro; SHIBATA Kanemitsu; GOTO Shunji; TOTANI Ryozo (Japanese Journal of National Medical Services, 1995)
The subjects studied were 148 patients who complained of postmenopausal bleeding. The thickness of endometrium (diameter of tumor) was measured by transvaginal ultrasonography and the sensitivity for detecting endometrial cancer was calculated. The sensitivity for detecting endometrial cancer according the thickness of endometrium was also assessed. Forty-two endometrial cancer patients underwent the preoperative measurement of the thickness of endomtrium and the relation between the thickness of endometrium and the infiltration into the muscular tunics was studied.Endometrial cancer was detected in 13 of 148 cases and the sensitivity was 8.8%. The sensitivities according to the thickness of endometrium were as follows; 0-5 mm (1.4%), 6-10 mm (2.5%), 11-15 mm (18.8%), 16-20 mm (25.0%), 21-5 mm (75.0%), over 26mm (50%). The sensitivity was significantly improved with increase in the thickness of endometrium.Of 16 patients suffering from endometrial cancer with the endometrium of less than 20 mm in thickness, 15 (93.8%) showed endometrial localization and infiltration with 0-1/3.These results suggest that the measurement of the thickness of endometrium by transvaginal urtrasonography provided the index for the detection of endometrial cancer and that this measurement method serves as a useful technique to make an early diagnosis of endometrial cancer. 閉経後出血148例を対象として, 経腟超音波による子宮内膜厚(腫瘍径)測定後, 子宮内膜癌検診を行い, 内膜癌検出率, および子宮内膜厚別内膜癌検出率を検討した. また, 術前に子宮内膜厚を測定した42例の内膜癌について, 子宮内膜厚と筋層浸潤の関係を検討した.内膜癌は148例のうち13例, 検出率は8.8%であった. 内膜厚別内膜癌検出率は0～5mm1.4%, 6～10mm2.5%, 11～15mm18.8%, 16～20mm25.0%, 21～25mm75.0%, 26mm以上50%であり, 検出率は内膜厚の上昇に伴い著しく増加した.子宮内膜厚と筋層浸潤の関係では, 内膜厚20mm以下の内膜癌16例のうち15例(93.8%)が内膜限局および0～1/3未満の浸潤であった.以上の成績は, 経腟超音波による子宮内膜厚測定が内膜癌検出の指標となるばかりでなく, 内膜癌の早期診断にも有用であることを示唆した.